Histamine type 1-receptor activation by low dose of histamine undermines human glomerular slit diaphragm integrity. (December 2016) - Veglia, Eleonora; Pini, Alessandro; Moggio, Aldo; Grange, Cristina; Premoselli, Federica; Miglio, Gianluca; Tiligada, Katerina; Fantozzi, Roberto; Chazot, Paul L.; Rosa, Arianna Carolina
Graphical abstract: Abstract: Histamine has been reported to decrease the ultrafiltration coefficient, which inversely correlates with glomerular permselectivity, however the mechanism(s) underling this effect have never been investigated. This study aimed to assess whether histamine could exert a direct detrimental effect on podocyte permeability and the possible involvement of two key proteins for the glomerular slit diaphragm (SD) integrity, zonula occludens-1 (ZO-1) and P-cadherin. The effect of histamine (100 pM–1000 nM) on coloured podocytes junctional integrity was evaluated functionally by a transwell assay of monolayer permeability and morphologically by electron microscopy. Histamine receptor (H1-4 R) presence was evaluated at both mRNA (RT-PCR) and protein (immunofluorescence) levels. The Kd and Bmax values for [ 3 H]mepyramine were determined by saturation binding analysis; IP1 and cAMP production evoked by histamine were measured by TR-FRET. ZO-1, P-cadherin and vimentin expression was assessed by qRT-PCR and quantitative immunoblotting. Histamine elicited a time- and sigmoidal dose-dependent (maximum effect at 8 h, 10 nM) increase in podocyte paracellular permeability widening the paracellular spaces. Only H1 R was predominantly localised to the podocyte membrane. Consistently, histamine elicited a sigmoidal dose-dependent increase in IP1, but not in cAMP. Histamine exposure evoked a concentration-dependent reduction in both ZO-1 and P-cadherin and a parallel induction of vimentin mRNA expression with a maximum effect after 6 h, and protein expression with a maximum effect after 8 h. These effects were prevented by the selective H1 R antagonist chlorpheniramine. In conclusion, our data demonstrate that histamine, via the H1 R, modifies SD morphological and functional integrity, in part, by decreasing the expression of ZO-1 and P-cadherin.